HUBUNGAN ANTARA PENERIMAAN DIRI DENGAN KONFORMITAS PADA PENGGUNA NARKOBA - Betanie Laim; Emmanuel Yuwono (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2026)
This study aims to determine the relationship between self-acceptance and conformity among drug users. The research employed a quantitative method with a correlational approach. The participants consisted of 51 individuals who had previously or were currently engaging in drug abuse. Data were collected using two psychological scales, namely the self-acceptance scale and the conformity scale, and were analyzed using the Pearson Product Moment correlation test with the aid of SPSS. The results showed a significant negative correlation between self-acceptance and conformity (r = –0.450; p = 0.001). This indicates that the higher an individual’s level of self-acceptance, the lower their tendency to conform to social pressure within drug-using groups. Conversely, the lower the level of self-acceptance, the higher the tendency to engage in conformity. These findings emphasize the importance of self-acceptance as a protective factor that plays a role in reducing the negative influence of social environments on drug abuse behavior.